1
$\begingroup$

Find the equation of the circle that touches these three lines $x= 0$, $y=0$, $x = a$.

Here is my attempt:

$x = 0$ and $y = 0$, these both line go through the $x$ and $y$ axes. And also the circle touches those two lines. So the center will be $C(p,p)$. That means $r = k = h = p$. The circle also touches the $x = a$ line. That means $r = a/2$. From that, I determined the center as $C(a/2, a/2)$.

The equation:

$$\left(x - \frac{a}{2}\right)^2 + \left(y - \frac{a}{2}\right)^2 = \left(\frac{a}{2}\right)^2$$

$$x^2 + y^2 - 2ax - 2ay + \frac{a^2}{4} = 0$$

which is not the correct answer.

Now can anyone tell me what's wrong with this attempt?

$\endgroup$
  • $\begingroup$ Be careful expanding your squares! $\endgroup$ – Blue Aug 7 at 16:44
1
$\begingroup$

Your error is very simple: you have wronged expanding the square, in fact $\left(x - \frac{a}{2}\right)^2 + \left(y - \frac{a}{2}\right)^2 = \left(\frac{a}{2}\right)^2$ is not $x^2 + y^2 - 2ax - 2ay + \frac{a^2}{4} = 0$, but: $$x^2-ax+\frac{a^2}{4}+y^2+ay=0$$ In other words: $$4x^2+4y^2-4ax-4ay+a^2=0$$

Also, by simmetry, I get $\left(x - \frac{a}{2}\right)^2 + \left(y + \frac{a}{2}\right)^2 = \left(\frac{a}{2}\right)^2$: $$4x^2+4y^2-4ax+4ay+a^2=0$$

To clarify, see this graph where $a=6$:

enter image description here

$\endgroup$
  • $\begingroup$ Also, by symmetry, is missing another solution: circle with center $(a/2,-a/2)$ and radius $a/2$. $\endgroup$ – Julian Mejia Aug 7 at 17:07
  • $\begingroup$ Yes, it's correct. $\endgroup$ – Matteo Aug 7 at 17:10
  • $\begingroup$ why (-a/2).I actually didn't get it.How did you get two solutions and if a is negative then It feels like c(+- a/2, +-a/2).I get confused>can you please explain. $\endgroup$ – Ghost Aug 7 at 17:17
  • $\begingroup$ @Ghost: see the graph in my answer. $\endgroup$ – Matteo Aug 7 at 17:30
  • $\begingroup$ Please check coefficients $4$ after expansion in last equations of both the numerators ! $\endgroup$ – Narasimham Aug 7 at 19:41
0
$\begingroup$

If the simple error in your calculation [coefficient in middle $2xy$ term in expansion of $(x+y)^2$ ] is removed the correct equation is

$$ (x^2+y^2)-a (x+y)+ \frac{a^2}{4}=0 $$

The origin/corner touching circle is in the first or fourth quadrant according as odd term $y$ is positive or negative.

$$ (x^2+y^2)-a (x-y)+ \frac{a^2}{4}=0 $$

Everything else is quite OK.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.